Injury, substance abuse, verbal abuse, and emotional and behavioral issues among adolescents in Uttarakhand, India: A categorical principal component analysis of global school-based health survey - Ranjeeta Kumari; Madhvi Dhamania; Sourabh Paul; Abhay Singh; Yogesh Singh; Bhola Nath (Indian Journal of Psychiatry)
Background: Adolescents in low-middle-income countries face increasing physical and mental health challenges. The present study aimed to assess status of injury, verbal abuse, substance use, and emotional behavior of adolescents of Uttarakhand, India, and evaluate the importance of each component. Methods: A cross-sectional study was conducted among adolescents in 13 government schools in Uttarakhand using the Global School-based Health Survey (GSHS). Categorical principal component analysis (CATPCA) using Varimax rotation was performed to analyze principal components among two domains of GSHS (substance abuse domain and verbal abuse and emotional behavior domain). Factorability was assessed using Kaiser–Meyer–Olkin and Bartlett’s test. Variance Accounted For index was used to evaluate the importance of each component. Results: A total of 634 adolescents completed the questionnaire. 41.3% students suffered from serious injury with a significant difference (P < 0.0001) between both genders. Girls were more likely to report having felt lonely most of the time or always in the past 12 months (11.0% vs 4.6%, P = 0.018). Boys were more likely to miss classes on 3 or more days (9.9% vs 4.9%, P = 0.043). Initiation of smoking cigarettes (9.6% vs 1.2%, P <0.0001) and tobacco chewing (3.4% vs 0.3%, P = 0.001) was more likely in 12–15-year-old boys. One-third of the students reported male guardians to use either alcohol or some form of tobacco. CATPCA yielded an 11-factor model accounting for 58.26% of variances with the most important principal component named “Tobacco (Smoking and Chewing): Initiation, Frequency and Attempt to Stop” (eigenvalue: 4.109). Conclusion: Significant differences in various items of injury, verbal abuse, substance use, and emotional behavior were recorded between boys and girls. CATPCA revealed patterns among injury, verbal abuse, emotional behavior, and substance abuse domains of GSHS by categorizing them into 11 components. On the basis of these patterns, prioritizing and development of appropriate school-based interventions may be implemented by various stakeholders of Uttarakhand.